Analog cosmology with two-fluid systems - Fifer, Zachary (2022)
Analog models in physics utilize a conceptual metaphore and a mathematical similarity to describe one system in terms of another. In this thesis, we will present the work that has been done regarding a time-dependent analog examining classical fluid interface waves in order to test predictions from cosmology. We will first detail theoretical work regarding interface waves in a strong-gradient magnetic field, conceived to simulate cosmological inflation, and constituting the first proposal for analog cosmology using interface waves. Motivated by this proposal we will then shift our focus towards parametric resonance, a process by which interface waves are exponentially amplified when coupled to an oscillating gravitational field.